Design and rationale of the ATHENA study – A 12-month, multicentre, prospective study evaluating the outcomes of a de novo everolimus-based regimen in combination with reduced cyclosporine or tacrolimus versus a standard regimen in kidney transplant patients: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Sommerer, Claudia; Suwelack, Barbara; Dragun, Duska; Schenker, Peter; Hauser, Ingeborg; Nashan, Björn; Thaiss, Friedrich
Abstract Background Immunosuppression with calcineurin inhibitors remains the mainstay of treatment after kidney transplantation; however, long-term use of these drugs may be associated with nephrotoxicity. In this regard, the current approach is to optimise available immunosuppressive regimens to reduce the calcineurin inhibitor dose while protecting renal function without affecting the efficacy. The ATHENA study is designed to evaluate renal function in two regimens: an everolimus and reduced calcineurin inhibitor-based regimen versus a standard treatment protocol with mycophenolic acid and tacrolimus in de novo kidney transplant recipients. Method/Design ATHENA is a 12-month, multicentre, open-label, prospective, randomised, parallel-group study in de novo kidney transplant recipients (aged 18 years or older) receiving renal allografts from deceased or living donors. Eligible patients are randomised (1:1:1) prior to transplantation to one of the following three treatment arms: everolimus (starting dose 1.5 mg/day; C0 3–8 ng/mL) with cyclosporineor everolimus (starting dose 3 mg/day; C0 3–8 ng/mL) with tacrolimusor mycophenolic acid (enteric-coated mycophenolate sodium at 1.44 g/day or mycophenolate mofetil at 2 g/day) with tacrolimus; in combination with corticosteroids. All patients receive induction therapy with basiliximab. The primary objective is to demonstrate non-inferiority of renal function (eGFR by the Nankivell formula) in one of the everolimus arms compared with the standard group at month 12 post transplantation. The key secondary objective is to assess the incidence of treatment failure, defined as biopsy-proven acute rejection, graft loss, or death, among the treatment groups. Other objectives include assessment of the individual components of treatment failure, incidence and severity of viral infections, incidence and duration of delayed graft function, incidence of indication biopsies, slow graft function and wound healing complications, and overall safety and tolerability. Exploratory objectives include evaluation of left ventricular hypertrophy assessed by the left ventricular mass index, evolution of human leukocyte antigen and non-human leukocyte antigen antibodies, and a cytomegalovirus substudy. Discussion As one of the largest European multicentre kidney transplant studies, ATHENA will determine whether a de novo everolimus-based regimen can preserve renal function versus the standard of care. This study further assesses a number of clinical issues which impact long-term outcomes post transplantation; hence, its results will have a major clinical impact. Trial registration Clinicaltrials.gov:NCT01843348, date of registration – 18 April 2013; EUDRACT number: 2011-005238-21, date of registration – 20 March 2012